TRENDS IN THE DEVELOPMENT OF “GREEN ARCHITECTURE”: FOREIGN AND DOMESTIC REPORTS - Polischuk, Vera; Kryzhanivskyi, Oleksandr (Theory and practice of design, 2023)
This article describes the main approaches in the design of residential and public complexes built according to the principles of «green architecture», which should create comfortable and energy-saving housing. The main principles of «green architecture» are highlighted, which are planned to be used in the design of the thesis in the future. Purpose is analysis of foreign and domestic experience in the design and operation of residential and public complexes built according to the principles of «green architecture». Methodology. It includes the following methods: compositional analysis; analysis of studies of residential and public complexes built according to the principles of «green architecture»; formalization method; comparative analysis; systematization and generalization of foreign and domestic experience. Results. As a result of the conducted research, the main characteristics in the design of residential and public complexes built according to the principles of «green architecture» were formulated and these principles were highlighted. The international and domestic experience of designing residential and public complexes built according to the principles of «green architecture» was analyzed. The issue of «green architecture» has been updated based on modern trends. The main directions and characteristics corresponding to the needs and values of society are highlighted. Examples of plans and facades of residential and public complexes built according to the principles of «green architecture» are given. The highlighted scientific materials became the starting point for understanding the researched issue. Scientific novelty. The peculiarities of the architectural and planning organization of residential and public complexes built according to the principles of «green architecture» and the prospects for development in Ukraine are characterized. The main principles in the design of this type of buildings are highlighted. Practical relevance. The results of the research can be used in the design and further research of residential and public complexes built according to the principles of «green architecture».